Understanding of derivative as an essential part of the study of differential calculus (2019)
The research aimed to design a teaching strategy and analyze benefits of its implementation in the use of technologies like GeoGebra and interactive materials that offers the web as enabling tools and teaching as mediation is aimed at students in grade 11 middle education. Tests pre-test and post-test and two experimental groups were applied control. It was verified that the teaching strategy has a positive influence on learning the experimental group improved the level of understanding of the concept of derivative and thus academic performance, in contrast to the control group to which is applied the traditional methodology.